EFFECT OF EXPORTS AND IMPORTS ON EAST JAVA ECONOMIC GROWTH 2011-2020 - Hidya Rinta; Edy Suhartono (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
"The Effect of Exports and Imports on Economic Growth in East Java Province for the Period 2011 - 2020". This research is motivated by the economic growth rate which shows an increase of 5.6% in East Java Province. This figure is certainly greater when compared to the national economic growth which increased by 5.4%. Economic growth in East Java certainly gets a contribution from foreign trade activities, namely exports and imports. In addition, the author's curiosity about the conditions of exports and imports in the province of East Java and their influence on economic growth also triggered the author to compose this thesis. especially with the existence of several business conditions in the country and in the world that can have a direct or indirect influence on international trade. This study aims to examine the effect of: (1) exports on economic growth in East Java Province, (2) imports on economic growth in East Java Province, and (4) exports together with imports on economic growth in East Java Province. This research uses a quantitative approach with the type of explanatory research. Sampling using non-probability sampling technique, while the data used is secondary data obtained from the Central Statistics Agency (BPS) East Java in 2011 2020. The data analysis method used in this research is multiple linear regression test. The results showed that (1) exports had an influence on economic growth in East Java Province, (2) imports had no effect on economic growth in East Java Province, and (4) exports together with imports had an influence on economic growth in Java Province. East.